READINESS OF LECTURERS TO OFFER ONLINE TEACHING AND LEARNING DURING CORONAVIRUS DISEASE-2019 AT THE UNIVERSITY OF LIMPOPO, SOUTH AFRICA - Rivoningo Nyiko; Witness Maluleke (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Understanding the perceptions of lecturers’ readiness to teach online during Coronavirus Disease-2019 (COVID-19) is essential, as their preparedness significantly influences the success of online learning outcomes. In addition, for lecturers to be properly ready for online Teaching and Leaning (T & L), it requires having the necessary skills, competencies, and infrastructures at their positions. Therefore, this study was conducted to determine the readiness of lecturers to offer online T & L during COVID-19 in one of the departments at the University of Limpopo (UL). A qualitative research approach was employed in this study to determine the lecturers’ readiness to offer online T & L. Because there is not much research done at UL regarding the readiness of lecturers to offer online T & L amid COVID-19, this qualitative study was exploratory in nature. The non-probability: Purposive sampling was adopted to select 10 participants. Data was collected using semi-structured Key Informant Interviews (KIIs) conducted by Google Forms and 9 out of the 10 participants completed the interview questions. Inductive Thematic Content Analysis (TCA) was applied to analyse the qualitative data. The findings of the study indicate that a significant number of lecturers experienced a lack of preparedness which was attributed mostly to inadequate training and limited prior experience with online digital platforms such as Blackboard. However, other findings highlight that the university took measures to mitigate the issue of readiness on lecturers by providing comprehensive training programmes. Moreover, the results showcase the need for continuous training and proactive adaptation to online T & L to sustain the readiness and effectiveness of online T & L. The study provides a set of recommendations for the university to enhance online T & L in response to the readiness of lecturers to offer online T & L starting from: The necessity of comprehensive institutional programmes that focus on both technological skills and pedagogical strategies to better equip lecturers, mentorship programmes to support lecturers, regular evaluations of training workshops are suggested and the university is urged to always have contingency plans for T & L and it is also recommended that UL should partner with other institutions to share insights in order to enhance online educational practices.